IMMU-02. PHASE I/II STUDY OF LASER INTERSTITIAL THERMOTHERAPY (LITT) COMBINED WITH CHECKPOINT INHIBITOR FOR RECURRENT GLIOBLASTOMA (RGBM): PRELIMINARY RESULTS. (21st September 2021) - Sloan, Andrew; Buerki, Robin; Murphy, Christopher
Abstract: BACKGROUND: Recurrent glioblastoma (rGBM) has poor response rate and survival. Laser Interstitial Thermotherapy (LITT), a minimally invasive approach, improves survival but is not curative alone. Previous studies of LITT suggested the possibility of an abscopal effect. Indeed, GBM are known to harbor elevated levels of immunosuppressive cells such as Treg, M2 macrophages and MDSC both in the tumor microenvironment as well as in the systemic circulation. Checkpoint inhibition (CPI) immunotherapy has proven highly effective for some solid tumors. CPI in newly diagnosed GBM demonstrated safety in phase I trials (NRG BN-002). Further, preclinical studies targeting PD-1 with concurrent RT appears to be synergistic and improve survival. We hypothesized that LITT would block tumor-induced immunosuppression and introduce tumor neoantigens. However, there was no data regarding safety of pembrolizumab combined with LITT. We thus conducted a phase I/II study of LITT + pembrolizumab starting at three times relative to LITT. METHODS: This is a three armed Phase I/II study based on timing of pembrolizumab (200 mg q 21 days) relative to LITT at 35d or 14d post-op, or 7d pre-op, with an expansion cohort phase II arm conducted at the earliest tolerated time of CPI administration. Adults with proven supratentorial rGBM with KPS >=70 and <= 2mg/d of dexamethasone were eligible. RESULTS: Arm 1-2 of the phase I trial demonstrated no SAEs grade II or greater, but limited evidence of response. Arm 3 (neoadjuvant) pembrolizumab appears to be equally safe and has been expanded to phase II, demonstrating at least two CR among the first 3 patients (66.6%) with >= 9 month follow-up and patients remain clinically stable at 10 and 15 months post-op. CONCLUSIONS: Neoadjuvant pembrolizumab combined with LITT for rGBM appears to be safe in this phase I trial, and demonstrates early evidence of response. The phase II trial is ongoing.